Manufacturing method for all-solid-state batteries

JP7637924B2Active Publication Date: 2025-03-03PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020562984
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-04
Publication Date
2025-03-03
Estimated Expiration
2039-12-04

AI Technical Summary

Benefits of technology

【0007】 本開示によれば、封止層による封止強度を十分に確保することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637924000001
    Figure 0007637924000001
  • Figure 0007637924000002
    Figure 0007637924000002
  • Figure 0007637924000003
    Figure 0007637924000003
Patent Text Reader

Abstract

An all-solid-state battery according to one aspect of the present disclosure includes an electrode layer, a solid electrolyte layer containing a solid electrolyte, and a sealing layer containing a sealing material, wherein at least one selected from the electrode layer and the solid electrolyte layer contains a binder, and the glass transition temperature of the sealing material is higher than the glass transition temperature of the binder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an all-solid-state battery and a method for manufacturing an all-solid-state battery. [Background technology]

[0002] Patent Documents 1 and 2 describe all-solid-state batteries that include a sealing layer in contact with a battery element. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-73374 A [Patent Document 2] JP 2012-38425 A Summary of the Invention [Problem to be solved by the invention]

[0004] In batteries using a solid electrolyte, a sealing layer may be provided for the purposes of preventing moisture from entering the inside of the battery and of maintaining the structure to prevent short circuits caused by contact between current collectors.

[0005] In the prior art, it is desirable to ensure the mechanical strength of a battery having a sealing layer. In order to ensure the mechanical strength of a battery, it is important to ensure sufficient sealing strength by the sealing layer. [Means for solving the problem]

[0006] The present disclosure relates to An electrode layer; a solid electrolyte layer including a solid electrolyte; a sealing layer including a sealing material; Equipped with At least one selected from the electrode layer and the solid electrolyte layer contains a binder, the glass transition temperature of the sealing material is higher than the glass transition temperature of the binder; Provides all-solid-state batteries. Effect of the Invention

[0007] According to the present disclosure, the sealing strength of the sealing layer can be sufficiently ensured. [Brief description of the drawings]

[0008] [Figure 1A] FIG. 1A is a schematic cross-sectional view of a battery according to one embodiment of the present disclosure. [Figure 1B] FIG. 1B is a schematic cross-sectional view of a battery according to a modified example. [Diagram 2] FIG. 2 is a flowchart showing an example of a method for manufacturing a battery. [Diagram 3] FIG. 3 is an experimental photograph of Sample 1. [Figure 4] FIG. 4 is an experimental photograph of Sample 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] (Findings on which this disclosure is based) From the viewpoint of increasing the area of ​​batteries, continuous production, and mass production, the application of a coating process to the manufacture of all-solid-state batteries has been considered. In the coating process, a slurry is prepared by dispersing raw material powder in a solvent. A coating film is formed by applying the slurry to a current collector by a coating method such as screen printing or die coating. The solvent is volatilized from the coating film by a thermal process using a drying oven or the like. This results in an electrode plate having a current collector and an electrode layer. Generally, a binder is added to the slurry to give the slurry a viscosity suitable for the coating process and to improve the strength of the electrode layer.

[0010] Thermoplastic resins are often used as binders. Some thermoplastic resins have a glass transition temperature. When a certain load is applied to a thermoplastic resin, it exhibits plastic deformation behavior at temperatures higher than the glass transition temperature and exhibits elastic deformation behavior at temperatures lower than the glass transition temperature.

[0011] A slurry containing a solid electrolyte is applied onto an electrode plate to form a coating film. The coating film is dried to form a solid electrolyte layer on the electrode plate. An electrode plate serving as a positive electrode and an electrode plate serving as a negative electrode are opposed to each other and pressed to obtain an all-solid-state battery. The electrode plate may be pressed before applying the slurry containing a solid electrolyte to improve the performance of the battery.

[0012] As a result of the intensive research conducted by the present inventors, it has now become clear for the first time that when the pressing temperature is lower than the glass transition temperature of the binder contained in at least one layer selected from the electrode layer and the solid electrolyte layer, the electrode plate warps. It is believed that the warping occurs for the following reasons. While the pressing pressure is applied and maintained, the particles (mainly the active material and the solid electrolyte) constituting the electrode layer move slightly to fill the gaps between each other. This increases the packing rate of the electrode layer. After a certain packing rate is achieved by a predetermined pressing pressure, the elongation of the electrode layer is mainly limited to a direction perpendicular to the pressing direction. In other words, the electrode layer elongates in a direction perpendicular to the pressing direction, so that tensile stress is generated in the electrode layer. Meanwhile, compressive stress is generated in the current collector in contact with the electrode layer. When the pressing temperature is lower than the glass transition temperature of the binder, when the load during pressing is removed, the binder contained in the electrode layer exhibits elastic deformation behavior, so that the binder tries to return to its original shape and original position. As a result, the electrode plate warps due to the tensile stress of the electrode layer and the compressive stress of the current collector. The positive and negative electrodes are warped so that the positive and negative electrodes approach each other at the center of the battery and move away from each other at the periphery of the battery. At the periphery of the battery, the electrode plate is warped in a direction in which the current collector moves away from the sealing layer. As a result, the sealing strength of the sealing layer is reduced. Thus, conventional all-solid-state batteries equipped with a sealing layer have problems such as the electrode layer peeling off from the current collector and insufficient sealing strength of the sealing layer.

[0013] (Summary of one aspect of the present disclosure) The battery according to the first aspect of the present disclosure comprises: An electrode layer; a solid electrolyte layer including a solid electrolyte; a sealing layer including a sealing material; Equipped with At least one selected from the electrode layer and the solid electrolyte layer contains a binder, The encapsulating material has a higher glass transition temperature than the binder.

[0014] According to the first aspect, it is possible to provide a battery in which the sealing strength provided by the sealing layer is sufficiently ensured.

[0015] In a second aspect of the present disclosure, for example, in the battery according to the first aspect, the electrode layer and the solid electrolyte layer may be laminated on each other, and the sealing layer may be in contact with at least one selected from a side surface of the electrode layer and a side surface of the solid electrolyte layer. With such a structure, the sealing strength of the sealing layer can be more sufficiently ensured.

[0016] In the third aspect of the present disclosure, for example, in the battery according to the first or second aspect, the binder may contain a thermoplastic resin. Thermoplastic resins are softened by heating to a temperature equal to or higher than the glass transition temperature and pressing. Therefore, when the binder contains a thermoplastic resin, the filling rate of the electrode layer and / or the solid electrolyte layer increases. Furthermore, since the electrode layer and / or the solid electrolyte layer can be easily molded by softening the binder, the pressing time can be shortened.

[0017] In a fourth aspect of the present disclosure, for example, in the battery according to the third aspect, the thermoplastic resin may include at least one selected from a styrene-butadiene copolymer and a styrene-ethylene-butadiene copolymer. When these copolymers are used as a binder, they exhibit good solubility even in a solvent with low polarity.

[0018] In a fifth aspect of the present disclosure, for example, in the battery according to any one of the first to fourth aspects, the glass transition temperature of the binder may be less than 120° C. In this temperature range, the glass transition temperature of the binder is lower than the pressing temperature, so that warping of the electrode plate can be suppressed.

[0019] In a sixth aspect of the present disclosure, for example, in the battery according to any one of the first to fifth aspects, the glass transition temperature of the sealing material may be equal to or higher than 120° C. In this temperature range, the glass transition temperature of the sealing material is higher than the glass transition temperature of the binder, so that the sealing strength of the sealing layer can be maintained.

[0020] In a seventh aspect of the present disclosure, for example, in the battery according to any one of the first to sixth aspects, the sealing material may contain polyimide. By containing a thermoplastic resin having a high glass transition temperature such as polyimide, the sealing strength of the sealing layer can be maintained even when the pressing temperature is high.

[0021] In an eighth aspect of the present disclosure, for example, in the battery according to any one of the first to seventh aspects, the electrode layer may contain the electrode active material and the solid electrolyte. By containing the electrode active material and the solid electrolyte, an efficient electrode layer can be produced.

[0022] A method for producing a battery according to a ninth aspect of the present disclosure includes the steps of: heating at least one selected from the electrode layer and the solid electrolyte layer to a pressing temperature; pressing at least one selected from the electrode layer and the solid electrolyte layer at the pressing temperature; Including, one or both of the electrode layer and the solid electrolyte layer to be pressed at the pressing temperature contain a binder; The pressing temperature is greater than the glass transition temperature of the binder.

[0023] According to the ninth aspect, the battery of the present disclosure can be efficiently manufactured.

[0024] In a tenth aspect of the present disclosure, for example, the method for producing a battery according to the ninth aspect may further include forming a sealing layer in contact with at least one selected from the electrode layer and the solid electrolyte layer, and when at least one selected from the electrode layer and the solid electrolyte layer is heated to the pressing temperature, the sealing layer may be heated to the pressing temperature, and when at least one selected from the electrode layer and the solid electrolyte layer is pressed, the sealing layer may be pressed at the pressing temperature. By providing a sealing layer, the mechanical strength of the battery can be ensured. Furthermore, by pressing the sealing material at the pressing temperature, the sealing strength provided by the sealing layer can be maintained.

[0025] In an eleventh aspect of the present disclosure, for example, in the method for producing a battery according to the tenth aspect, the glass transition temperature of the sealing material constituting the sealing layer may be higher than the glass transition temperature of the binder. When the glass transition temperature of the sealing material is higher than the glass transition temperature of the binder, the sealing strength of the sealing layer can be maintained, and therefore the mechanical strength of the all-solid-state battery can be maintained.

[0026] In the twelfth aspect of the present disclosure, for example, in the method for producing a battery according to the eleventh aspect, the glass transition temperature of the sealing material constituting the sealing layer may be higher than the pressing temperature. When the glass transition temperature of the sealing material is higher than the pressing temperature, the sealing material does not undergo plastic deformation. As a result, the sealing strength of the sealing layer can be maintained, and therefore the mechanical strength of the all-solid-state battery can be maintained.

[0027] (Embodiment) Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0028] [Structure of all-solid-state batteries] FIG. 1A is a schematic cross-sectional view of an all-solid-state battery 10 according to an embodiment. As shown in FIG. 1A, the all-solid-state battery 10 includes a positive electrode 11, a negative electrode 12, a solid electrolyte layer 5, and a sealing layer 8. The positive electrode 11 includes a positive electrode current collector 3 and a positive electrode layer 4. The negative electrode 12 includes a negative electrode current collector 6 and a negative electrode layer 7. The positive electrode layer 4 is disposed on the positive electrode current collector 3. The negative electrode layer 7 is disposed on the negative electrode current collector 6. The solid electrolyte layer 5 is disposed between the positive electrode layer 4 and the negative electrode layer 7. The solid electrolyte layer 5 is in contact with each of the positive electrode layer 4 and the negative electrode layer 7. The sealing layer 8 is in contact with the positive electrode current collector 3 and the negative electrode current collector 6. The positive electrode layer 4 and the negative electrode layer 7 are each an example of an electrode layer. The positive electrode 11 and the negative electrode 12 are each an example of an electrode plate. The sealing layer 8 can suppress the intrusion of moisture into the all-solid-state battery 10 and maintain the structure of the all-solid-state battery 10 to prevent a short circuit due to contact between the positive electrode current collector 3 and the negative electrode current collector 6. As a result, the mechanical strength of the all-solid-state battery 10 can be ensured.

[0029] When the all-solid-state battery 10 is viewed from above, the sealing layer 8 has a frame shape. The positive electrode layer 4, the solid electrolyte layer 5, and the negative electrode layer 7 are surrounded by the sealing layer 8. The positive electrode current collector 3 is in contact with the lower surface of the sealing layer 8, and the negative electrode current collector 6 is in contact with the upper surface of the sealing layer 8.

[0030] In this embodiment, the sealing layer 8 is in contact with the side surface 5t of the solid electrolyte layer 5. With this structure, the sealing strength by the sealing layer 8 can be more sufficiently ensured. The sealing layer 8 is not in contact with the positive electrode layer 4 and the negative electrode layer 7. With this structure, the sealing material and the electrode material are less likely to react in the production of the all-solid-state battery 10. In other words, the risk of deterioration of the battery performance can be avoided. In the production of the all-solid-state battery, if the sealing material is impregnated into the electrode layer, the impregnated portion cannot function as an electrode. As a result, the battery performance is deteriorated. In this embodiment, since the electrode layer is produced before the sealing layer 8, the above-mentioned problem is less likely to occur, and it is easy to specify the area of ​​the electrode that contributes to power generation. In addition, even if the battery is mass-produced, the battery performance is less likely to be deteriorated.

[0031] FIG. 1B is a schematic cross-sectional view of an all-solid-state battery 10B according to a modified example. In the all-solid-state battery 10B according to this modified example, the side surface 4t of the positive electrode layer 4, the side surface 7t of the negative electrode layer 7, and the side surface 5t of the solid electrolyte layer 5 are in contact with the sealing layer 8. With this structure, the sealing strength of the sealing layer 8 can be more sufficiently ensured. In addition, since the volume of the solid electrolyte layer 5 can be reduced, it is expected that the manufacturing cost of the all-solid-state battery 10B can be reduced due to the reduction in material costs. The other configurations of the all-solid-state battery 10B are the same as those of the all-solid-state battery 10.

[0032] Each component of the all-solid-state battery 10 will be described in detail.

[0033] (Positive electrode 11 and negative electrode 12) The positive electrode 11 includes a positive electrode current collector 3 and a positive electrode layer 4. The negative electrode 12 includes a negative electrode current collector 6 and a negative electrode layer .

[0034] The material of the positive electrode current collector 3 and the negative electrode current collector 6 is not particularly limited, and materials generally used in lithium ion batteries can be used. The material of the positive electrode current collector 3 may be the same as or different from the material of the negative electrode current collector 6. Examples of the material of the positive electrode current collector 3 and the negative electrode current collector 6 include copper, copper alloy, aluminum, aluminum alloy, stainless steel, nickel, titanium, carbon, lithium, indium, and conductive resin. The shape of the positive electrode current collector 3 and the negative electrode current collector 6 is also not particularly limited. Examples of the shape of the positive electrode current collector 3 and the negative electrode current collector 6 include foil, film, and sheet. The surfaces of the positive electrode current collector 3 and the negative electrode current collector 6 may be provided with irregularities.

[0035] The electrode layer includes an active material. The composition of the active material is not particularly limited and can be selected according to the required function. The electrode layer may include other materials such as a conductive material, a solid electrolyte, and a binder, as necessary.

[0036] Active materials are generally classified into positive electrode active materials and negative electrode active materials, and the positive electrode active material and the negative electrode active material are selected depending on the required function.

[0037] Examples of the positive electrode active material include lithium-containing transition metal oxides, vanadium oxides, chromium oxides, and lithium-containing transition metal sulfides. Examples of the lithium-containing transition metal oxides include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNiCoMnO2, LiNiCoO2, LiCoMnO2, LiNiMnO2, LiNiCoMnO4, LiMnNiO4, LiMnCoO4, LiNiCoAlO2, LiNiPO4, LiCoPO4, LiMnPO4, LiFePO4, Li2NiSiO4, Li2CoSiO4, Li2MnSiO4, Li2FeSiO4, LiNiBO3, LiCoBO3, LiMnBO3, and LiFeBO3. Examples of the lithium-containing transition metal sulfides include LiTiS2, Li2TiS3, and Li3NbS4. One or more of these positive electrode active materials may be used.

[0038] Examples of the negative electrode active material include carbon materials, lithium alloys, metal oxides, lithium nitride (Li3N), metallic lithium, and metallic indium. Examples of the carbon material include artificial graphite, graphite, non-graphitizable carbon, and easily graphitizable carbon. Examples of the lithium alloy include an alloy of lithium and at least one metal selected from the group consisting of Al, Si, Pb, Sn, Zn, and Cd. Examples of the metal oxide include LiFe2O3, WO2, MoO2, SiO, and CuO. A mixture or a composite of a plurality of materials may be used as the negative electrode active material.

[0039] The shape of the positive electrode active material and the negative electrode active material is not particularly limited, and may be, for example, particulate. The size of the positive electrode active material and the negative electrode active material is also not particularly limited. When each of the positive electrode active material and the negative electrode active material is particulate, the average particle size of the particles of the positive electrode active material and the average particle size of the particles of the negative electrode active material may be 0.5 μm or more and 20 μm or less, or 1 μm or more and 15 μm or less. The average particle size may be, for example, a median diameter (d50) measured using a particle size distribution measuring device.

[0040] When the particle size distribution cannot be measured, the average particle size of the particles can be calculated by the following method. The particle group is observed under an electron microscope, and the area of ​​a specific particle in the electron microscope image is calculated by image processing. When only the particle group cannot be directly observed, a structure containing the particles is observed under an electron microscope, and the area of ​​a specific particle in the electron microscope image is calculated by image processing. The diameter of a circle having an area equal to the calculated area is regarded as the diameter of that specific particle. The diameters of an arbitrary number of particles (for example, 10 particles) are calculated, and their average value is regarded as the average particle size of the particles.

[0041] The conductive material is not particularly limited and can be appropriately selected from those generally used in lithium ion batteries. Examples of the conductive material include graphite, carbon black, conductive fibers, conductive metal oxides, and organic conductive materials. These conductive materials may be used alone or in combination of two or more.

[0042] The solid electrolyte is not particularly limited, and can be appropriately selected from those generally used in lithium ion batteries according to the type of active material and the application of the all-solid-state battery 10. Examples of the solid electrolyte include sulfide-based solid electrolyte materials, oxide-based solid electrolyte materials, other inorganic solid electrolyte materials, and organic solid electrolyte materials. The solid electrolyte may be used alone or in combination of two or more types. The shape of the solid electrolyte is not particularly limited, and examples thereof include particulate forms. The size of the solid electrolyte is also not particularly limited. When the solid electrolyte is particulate, the average particle size of the solid electrolyte particles may be 0.01 μm or more and 15 μm or less, or 0.2 μm or more and 10 μm or less. The average particle size may be, for example, a median diameter (d50) measured using a particle size distribution measuring device.

[0043] The binder is not particularly limited and may be appropriately selected from those generally used in lithium ion batteries. Examples of binders include thermoplastic resins. Examples of thermoplastic resins include thermoplastic elastomers such as styrene-butadiene copolymers and styrene-ethylene-butadiene copolymers. When preparing a slurry, a solvent with low polarity may be used to prevent a decrease in the performance of the solid electrolyte, such as ion conductivity. Styrene-butadiene copolymers or styrene-ethylene-butadiene copolymers exhibit good solubility in solvents with low polarity when preparing a slurry. Therefore, the use of these polymers can prevent a decrease in the performance of the solid electrolyte. Other examples of thermoplastic resins include ethyl cellulose, polyvinylidene fluoride, polyethylene, polypropylene, polyisobutylene, polystyrene, polyvinyl chloride, polyvinyl acetate, polymethyl methacrylate, polyethyl methacrylate, polyn-propyl methacrylate, polyn-butyl methacrylate, polydimethylsiloxane, cis-1,4-polybutadiene, polyisoprene, nylon-6, nylon-6,6, polyethylene terephthalate, and polyvinyl alcohol. These binders may be used alone or in combination of two or more kinds.

[0044] The glass transition temperature of the binder is lower than the glass transition temperature of the sealing material described later. The glass transition temperature of the binder may be 100°C or higher, or may be 120°C or higher. When the glass transition temperature of the binder is lower than the glass transition temperature of the sealing material, the pressing temperature can be set between the glass transition temperature of the binder and the glass transition temperature of the sealing material. That is, the pressing temperature is higher than the glass transition temperature of the binder and lower than the glass transition temperature of the sealing material. When the temperature difference is sufficiently large, the pressing temperature is easily set to a temperature between the glass transition temperature of the binder and the glass transition temperature of the sealing material, so that the pressing process can be easily carried out.

[0045] The glass transition temperature can be measured using thermomechanical analysis (TMA), dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC), differential scanning calorimetry (DTA), and the like.

[0046] (Solid electrolyte layer 5) The material of the solid electrolyte layer 5 is not particularly limited, and can be appropriately selected from those generally used in lithium ion batteries according to the type of active material and the application of the all-solid-state battery 10. Examples of the material of the solid electrolyte layer 5 include sulfide-based solid electrolyte materials, oxide-based solid electrolyte materials, other inorganic solid electrolyte materials, and organic solid electrolyte materials. The solid electrolyte may be used alone or in combination of two or more types. The shape of the solid electrolyte is not particularly limited, and examples thereof include particulate forms. The size of the solid electrolyte is also not particularly limited. When the solid electrolyte is particulate, the average particle size of the solid electrolyte particles may be 0.01 μm or more and 15 μm or less, or 0.2 μm or more and 10 μm or less. The average particle size may be, for example, a median diameter (d50) measured using a particle size distribution measuring device.

[0047] (Sealing layer 8) A thermoplastic resin having a high glass transition temperature can be used as the sealing material constituting the sealing layer 8. An example of a thermoplastic resin having a high glass transition temperature is polyimide. By using polyimide, the sealing strength of the sealing layer 8 can be maintained even when the pressing temperature is high. In other words, since the pressing temperature range can be set to the high temperature side, the all-solid-state battery 10 can be efficiently manufactured. Furthermore, since the glass transition temperature range of the binder can also be set to the high temperature side, more types of binders can be used. Other examples of thermoplastic resins that can be used as the sealing material include poly-α-methylstyrene, polycarbonate, polyacrylonitrile, etc. Furthermore, thermosetting resins and photocurable resins may be used as the sealing material. These may be used alone or in combination of two or more types. When the glass transition temperature of the sealing material is sufficiently high, the sealing strength of the sealing layer can be sufficiently maintained.

[0048] To enhance the function of the sealing layer 8, the sealing material may contain other materials such as functional powders, fibers, etc. Examples of other materials include inorganic fillers, silica gel, etc. The inorganic fillers can enhance the structural retention. The silica gel can enhance the water resistance. These functional powders or fibers may be used alone or in combination of two or more types.

[0049] The glass transition temperature of the sealing material is higher than the glass transition temperature of the binder. The glass transition temperature of the sealing material may be 120°C or higher. The difference between the glass transition temperature of the sealing material and the glass transition temperature of the binder is, for example, 10°C or higher and 60°C or lower. When the glass transition temperature of the sealing material is higher than the glass transition temperature of the binder, the pressing temperature can be set between the glass transition temperature of the sealing material and the glass transition temperature of the binder. That is, the pressing temperature is higher than the glass transition temperature of the binder and lower than the glass transition temperature of the sealing material. When the temperature difference is sufficiently large, the pressing temperature can be easily set to a temperature between the glass transition temperature of the binder and the glass transition temperature of the sealing material, so that the pressing process can be easily carried out.

[0050] [Manufacturing method of all-solid-state batteries] Next, a description will be given of an example of a method for manufacturing the all-solid-state battery 10. FIG.

[0051] First, in step S1, the positive electrode 11 and the negative electrode 12 are prepared. A mixture containing a positive electrode active material or a negative electrode active material and, if necessary, other materials such as a conductive material, a solid electrolyte, and a binder is prepared. The mixing ratio of each material is appropriately determined depending on the intended use of the battery. Next, the mixture is mixed by a mixer. The mixer is not particularly limited, and a known device can be used. Examples of the mixer include a planetary mixer and a ball mill. However, the method of mixing the materials is not particularly limited.

[0052] Next, the mixture containing the active material is applied to a predetermined thickness on the current collector, thereby obtaining an electrode plate having a current collector and an electrode layer.

[0053] Another method for producing an electrode plate is as follows. First, a mixture containing an active material is dispersed in an appropriate solvent to prepare a slurry. The slurry is applied to a positive electrode collector 3 or a negative electrode collector 6 to form a coating film. The coating film is then dried to produce an electrode plate. Examples of methods for applying the slurry include a screen printing method, a die coating method, a spray method, and a doctor blade method.

[0054] Next, in step S2, the solid electrolyte layer 5 is prepared. The method for preparing the solid electrolyte layer 5 is not particularly limited, and a known method can be used. First, a mixture containing a solid electrolyte and a binder is prepared. The mixing ratio of each material is appropriately determined depending on the intended use of the all-solid-state battery 10. Next, the mixture is mixed by a mixer. The mixer is not particularly limited, and a known device can be used. Examples of the mixer include a planetary mixer and a ball mill. However, the method for mixing the materials is not particularly limited.

[0055] A mixture containing a solid electrolyte is deposited to a predetermined thickness on the positive electrode layer 4 or the negative electrode layer 7. In this way, the solid electrolyte layer 5 is formed.

[0056] Another method for producing the solid electrolyte layer 5 is as follows. First, a mixture containing a solid electrolyte is dispersed in an appropriate solvent to prepare a slurry. The slurry is applied onto the positive electrode layer 4 or the negative electrode layer 7 to form a coating film. The coating film is then dried to produce the solid electrolyte layer 5. Examples of methods for applying the slurry include a screen printing method, a die coating method, a spray method, and a doctor blade method.

[0057] Yet another method for producing the solid electrolyte layer 5 is as follows. The above-mentioned slurry is applied onto a support material to form a coating film. The coating film is dried to obtain a solid electrolyte sheet. The solid electrolyte sheet is transferred from the support material onto the positive electrode 11 or the negative electrode 12, whereby the solid electrolyte layer 5 disposed on the positive electrode 11 or the negative electrode 12 can be produced.

[0058] The binder may be contained in at least one selected from the group consisting of the positive electrode layer 4, the negative electrode layer 7, and the solid electrolyte layer 5. The binder may be contained in all of the positive electrode layer 4, the negative electrode layer 7, and the solid electrolyte layer 5. The composition of the binder contained in the positive electrode layer 4 may be the same as or different from the composition of the binder contained in the solid electrolyte layer 5. The composition of the binder contained in the negative electrode layer 7 may be the same as or different from the composition of the binder contained in the solid electrolyte layer 5. The composition of the binder contained in the positive electrode layer 4 may be the same as or different from the composition of the binder contained in the negative electrode layer 7.

[0059] Next, in step S3, the sealing layer 8 is produced. The method for producing the sealing layer 8 is not particularly limited, and a known method can be used. For example, a sealing material is applied to the electrode plate so as to be in contact with at least one selected from the electrode layer and the solid electrolyte layer 5. The sealing material may be in contact with at least one selected from the positive electrode current collector 3 and the negative electrode current collector 6. Examples of the method for applying the sealing material include a screen printing method, an inkjet method, and a coating method using a dispenser. The sealing layer 8 is formed by drying the sealing material as necessary.

[0060] Thereafter, the positive electrode 11 and the negative electrode 12 are laminated to obtain an assembly of the positive electrode 11, the solid electrolyte layer 5, the negative electrode 12, and the sealing layer 8. The positive electrode layer 4 is disposed on the positive electrode current collector 3, and the negative electrode layer 7 is disposed on the negative electrode current collector 6. The solid electrolyte layer 5 is disposed between the positive electrode layer 4 and the negative electrode layer 7.

[0061] Next, in step S4, at least one layer selected from the electrode layer and the solid electrolyte layer 5 is heated to a pressing temperature. In this embodiment, for example, when a flat plate press is used, the assembly can be heated to the pressing temperature by heating the plate in contact with the assembly during pressing. When a roll press is used, the assembly can also be heated to the pressing temperature by heating the roll.

[0062] Next, in step S5, at least one layer selected from the electrode layer and the solid electrolyte layer 5 is pressed at a pressing temperature. Specifically, the assembly is pressed so that a load is applied in the thickness direction of each layer. At this time, at least one layer selected from the electrode layer and the solid electrolyte layer 5 contains a binder, and the layer containing the binder is pressed at the pressing temperature. In addition, the pressing temperature is higher than the glass transition temperature of the binder. By pressing while heating, the filling rate of the active material and the solid electrolyte is increased, and the contact interface between the particles of the active material and the particles of the solid electrolyte is increased. As a result, the performance of the all-solid-state battery 10 is improved. The "electrode layer" is at least one selected from the positive electrode layer 4 and the negative electrode layer 7.

[0063] The electrode layers and solid electrolyte layer 5 may be individually heated to a pressing temperature and pressed, and then an assembly may be formed, and the assembly may be heated and pressed to obtain the all-solid-state battery 10.

[0064] The pressing temperature is specified by, for example, the surface temperature of the current collector. However, when the heat capacity of the plate or the roll is sufficiently larger than the heat capacity of the target, the pressing temperature may be, for example, the surface temperature of the plate or the roll. "Pressing at the pressing temperature" means pressing while maintaining the target at the pressing temperature.

[0065] In this embodiment, when the assembly is heated to the pressing temperature, the sealing layer 8 is also heated to the pressing temperature. When the assembly is pressed at the pressing temperature, the sealing layer 8 is also pressed at the pressing temperature. Specifically, the entire assembly can be pressed at the pressing temperature so that a load is applied in the thickness direction of each layer. Therefore, the all-solid-state battery 10 can be easily manufactured. Furthermore, by heating the sealing layer 8 to the pressing temperature and pressing it, the sealing strength provided by the sealing layer 8 is maintained. As a result, the performance of the all-solid-state battery 10 is improved.

[0066] Through the above steps, the all-solid-state battery 10 is obtained.

[0067] If the pressing temperature is lower than the glass transition temperature of the binder, the binder will deform elastically when the electrode layer and / or solid electrolyte layer are pressed. When the binder dispersed in the grain boundaries of the particles of the electrode active material and the particles of the solid electrolyte deforms elastically, a part of the load applied by pressing deforms the electrode layer and / or solid electrolyte layer in a direction perpendicular to the pressing direction. When the load applied by pressing is removed, the binder tries to return to its original shape and original position. As a result, the electrode plate warps. In the case of a configuration in which the electrode layer is on top and the current collector is on the bottom, the electrode plate warps in an upward convex shape. In the case of a configuration in which the electrode layer is on the bottom and the current collector is on top, the electrode plate warps in a downward convex shape. Since the positive electrode layer and the negative electrode layer face each other, the positive electrode and the negative electrode warp so that the positive electrode and the negative electrode approach each other at the center of the battery and move away from each other at the outer periphery of the battery. Therefore, the distance between the end of the positive electrode current collector and the end of the negative electrode current collector becomes large, and as a result, the sealing strength by the sealing layer decreases.

[0068] Furthermore, if the electrode plate is significantly warped, cracks may occur between the electrode layer and the current collector, or the electrode layer may peel off from the current collector, which may result in a decrease in battery performance.

[0069] In contrast, in this embodiment, the pressing temperature is higher than the glass transition temperature of the binder. Therefore, the binder undergoes plastic deformation during pressing at the pressing temperature. The binder, which is dispersed in the particles of the electrode active material and the grain boundaries of the solid electrolyte, acts to reduce the gaps between the particles by pressing. As a result, the binder undergoes plastic deformation. That is, the electrode layer elongates in a direction perpendicular to the pressing direction, and the binder undergoes plastic deformation accordingly. Therefore, even if the load caused by the press is removed, the elongation in the direction perpendicular to the pressing direction is greatly suppressed. The sealing layer 8 is not pulled away from the end of the positive electrode collector 3 and the end of the negative electrode collector 6, so that the sealing strength can be maintained.

[0070] When the pressing temperature is higher than the glass transition temperature of the binder, the binder exhibits plastic deformation behavior. Although the binder also deforms in the direction of deformation of the electrode layer caused by pressing, the stress that tries to restore the binder to its original shape is alleviated even when the load of the press is removed. In other words, the tensile stress of the electrode layer is alleviated. As a result, the warping of the electrode plate is significantly suppressed, and the sealing strength can be maintained.

[0071] The difference between the pressing temperature and the glass transition temperature of the binder is, for example, 0° C. or more and 40° C. or less. When the pressing temperature is higher than the glass transition temperature of the binder, the binder can be sufficiently plastically deformed when pressed, so that deformation of the pressed electrode layer and / or solid electrolyte layer 5 can be suppressed. In other words, warping of the electrode plate is suppressed, so that the sealing layer 8 and the current collector are less likely to peel off. Since the sealing strength of the sealing layer 8 is sufficiently ensured, an all-solid-state battery 10 having high mechanical strength can be provided.

[0072] The glass transition temperature of the sealing material is, for example, higher than the glass transition temperature of the binder. In this case, the pressing temperature may be higher than the glass transition temperature of the sealing material. When the pressing temperature is higher than the glass transition temperature of the sealing material, the sealing material is plastically deformed by pressing at the pressing temperature. However, when the difference between the glass transition temperature of the sealing material and the glass transition temperature of the binder is large, the plastic deformation of the sealing material is suppressed more than the plastic deformation of the binder. As a result, the sealing strength of the sealing layer 8 is sufficiently ensured, and an all-solid-state battery 10 having high mechanical strength can be provided.

[0073] The glass transition temperature of the sealing material may be higher than the pressing temperature. The difference between the glass transition temperature of the sealing material and the pressing temperature is, for example, higher than 0°C and not higher than 20°C. When the glass transition temperature of the sealing material is higher than the pressing temperature, the sealing material is not plastically deformed by pressing, so that the shape of the sealing layer 8 is maintained. Therefore, in the produced all-solid-state battery 10, the sealing strength of the sealing layer 8 is sufficiently ensured, so that an all-solid-state battery 10 having high mechanical strength can be provided.

[0074] As described above, when the pressing temperature is higher than the glass transition temperature of the binder and lower than the glass transition temperature of the sealing material, it is possible to maintain the sealing strength of the sealing layer 8 while suppressing warping of the electrode plate. This ensures the mechanical strength of the all-solid-state battery 10 including the sealing layer 8. EXAMPLES

[0075] The present disclosure will be described in more detail below with reference to examples. The following examples are merely illustrative, and the present disclosure is not limited to the following examples.

[0076] (Sample 1) The solid electrolyte and binder were mixed to obtain a mixture. The mixture was applied onto the current collector by a coating process. This resulted in an electrode plate having a current collector and a solid electrolyte layer. Styrene-ethylene-butylene-styrene-based thermoplastic elastomer (Tuftec M1913, glass transition temperature 90°C, manufactured by Asahi Kasei Corporation) was used as the binder. The electrode plate was placed on a metal plate heated to 120°C, heated to the pressing temperature, and pressed at the pressing temperature. The pressing temperature was set to 120°C. The heated metal plate was sufficiently thicker than the electrode plate and the difference in heat capacity was sufficiently large, so the temperature of the metal plate was taken as the temperature of the electrode plate. The temperature of the metal plate was measured using a thermocouple installed inside the plate.

[0077] (Sample 2) An electrode plate was obtained in the same manner as in Sample 1, except that the pressing temperature was set to 25° C. (room temperature).

[0078] Photographs of the electrode plate after pressing are shown in Figures 3 and 4.

[0079] 3, warping of the electrode plate after pressing was suppressed in the electrode plate of Sample 1. Warping of the electrode plate was suppressed by pressing at a temperature higher than the glass transition temperature of the binder.

[0080] On the other hand, as shown in Fig. 4, the electrode plate of Sample 2 was significantly warped after pressing. In other words, the warping of the electrode plate could not be suppressed by pressing at a temperature lower than the glass transition temperature of the binder. [Industrial Applicability]

[0081] The technology of the present disclosure is useful for batteries in portable information terminals, portable electronic devices, home power storage devices, motorcycles, electric vehicles, hybrid electric vehicles, and the like. [Explanation of symbols]

[0082] 3 Positive electrode current collector 4 Positive electrode layer 4t Positive electrode layer side 5 Solid electrolyte layer 5t Side of solid electrolyte layer 6 Negative electrode current collector 7. Negative electrode layer 7t Side of negative electrode layer 8 Sealing layer 10,10B solid state battery 11 Positive electrode 12 Negative electrode

Claims

1. heating at least one selected from the electrode layer and the solid electrolyte layer to a pressing temperature; pressing at least one selected from the electrode layer and the solid electrolyte layer at the pressing temperature in a state in which the electrode layer is disposed between a current collector and the solid electrolyte layer in a thickness direction of the electrode layer; forming a sealing layer in contact with at least one selected from the electrode layer and the solid electrolyte layer; Including, one or both of the electrode layer and the solid electrolyte layer to be pressed at the pressing temperature contain a binder; the pressing temperature is greater than the glass transition temperature of the binder; When at least one selected from the electrode layer and the solid electrolyte layer is heated to the pressing temperature, the sealing layer is heated to the pressing temperature; When pressing at least one selected from the electrode layer and the solid electrolyte layer, the sealing layer is pressed at the pressing temperature. How solid-state batteries are manufactured.

2. The glass transition temperature of the sealing material constituting the sealing layer is higher than the glass transition temperature of the binder. The method for producing the all-solid-state battery according to claim 1 .

3. The glass transition temperature of the sealing material constituting the sealing layer is higher than the pressing temperature. The method for producing the all-solid-state battery according to claim 2 .

Citation Information

Patent Citations

  • Method of manufacturing electrode body, and electrode body

    JP2012038425A

  • Method for manufacturing all-solid secondary battery

    JP2012243476A

  • Resin solution composition, and method for manufacturing display body

    JP2015147917A

  • All-solid lithium battery

    JP2016033880A

  • Bipolar type lithium ion battery and manufacturing method thereof

    JP2017073374A